Ecological and human health risk assessment of antimony (Sb) in surface and drinking water in China. (10th October 2021) - Tao, Yanru; Su, Hailei; Li, Huixian; Zhu, Yuanrong; Shi, Di; Wu, Fengchang; Sun, Fuhong
Abstract: Antimony (Sb) persists in environmental media and can be toxic to aquatic organisms and humans. Although China is the primary Sb-producing country, the levels of Sb contamination and their potential risk to water resources remain unclear. This study provides an overview of Sb contamination in surface water and centralized drinking water sources across China and assesses its potential ecological and human health risks. Species sensitivity distribution was used to derive acute and chronic aquatic life criteria for Sb, which were 511.7 μg/L and 148.3 μg/L, respectively. Zooplankton were determined to be the most sensitive species, and fish were the least sensitive. Sb contamination in China is more serious than other countries. Risk quotients were used to assess the ecological risks of Sb. Chronic ecological risk quotients of 0.0013–27.39 were identified for surface water located near Sb mines. The highest values indicate high risk, particularly for zooplankton species. Exposure characteristics for the Chinese population across age group, sex, season, and region were used to assess the non-carcinogenic risk of Sb in centralized drinking water sources in China. Hazard quotients of 0.001–0.99 were found for these centralized drinking water sources. The non-carcinogenic risk posed by Sb was acceptable in the majority of locations, except in Hunan Province, which had the highest hazard quotient (approximately 1). This province contains the main Sb mining area in China, which poses a relatively large threat to human health. The Sb health risk for children was significantly higher than adults, but there was no significant difference in risk between men and women. The Sb drinking water guidance value to protect human health was calculated to be 19.65 μg/L for Chinese population. The results of this ecological and human health risk assessment highlight the importance of clean Sb production to reduce the negative effects of Sb contamination in China. Graphical abstract: Image 1 Highlights: Antimony (Sb) constitutes an ecological risk in surface water near mines in China. Sb poses a high health risk to residents in Southern China. The acute and chronic Sb criteria for native Chinese freshwater organisms are 511.7 and 148.3 μg/L, respectively. The Sb drinking water guidance value to protect human health is recommended to be 19.65 μg/L for the Chinese population.